ANALISIS PENGARUH KURS RUPIAH, CADANGAN DEVISA DAN THE FED RATE TERHADAP SUKU BUNGA DI INDONESIA DALAM PERSPEKTIF EKONOMI ISLAM TAHUN 2003-2024 DENGAN PENDEKATAN VECM - Al lamsa, Salman; Malik, Anas; Ningsih, Nur Wahyu (Investama : Jurnal Ekonomi dan Bisnis, 2025)
This study aims to analyze the influence of rupiah exchange rate, foreign exchange reserves, and The Fed Rate on interest rates in Indonesia from an Islamic economic perspective for the period 2003-2024 using the Vector Error Correction Model (VECM) approach. This research uses a quantitative approach with time series data for 22 years (2003-2024) and analyzes data using Eviews 10. The results show that in the long term, the rupiah exchange rate has a significant effect on interest rates in Indonesia (t-statistic 2.93 > t-table 2.10), The Fed Rate has a significant effect on interest rates (t-statistic 2.67 > t-table 2.10), while foreign exchange reserves do not significantly affect interest rates (t-statistic 1.85 < t-table 2.10). From an Islamic economic perspective, interest rates are a manifestation of usury (riba) practices that are prohibited because they contain elements of exploitation and injustice. Islamic financial systems develop comprehensive alternatives through profit-sharing principles (mudharabah), buying and selling (murabahah), and leasing (ijarah) that reflect dimensions of justice and blessing. This research provides an important contribution to monetary policy making that considers national economic stability while still referring to Islamic economic principles.